Technology integration in service-learning pedagogy: A holistic framework - Salam, M.; Awang Iskandar, D/N.; Ibrahim, D.H.A.; Farooq, M.S. (Elsevier Ltd, 2019)
Service learning is an experiential learning approach, which intentionally integrates community service with classroom learning, as it provides real-world learning experience for students to gain practical knowledge from hands-on field experience. In order to enhance students’ better understanding of course contents and theoretical knowledge, increasing number of academicians are incorporating service learning in their curriculum. However, less attention has been given to the effective integration of technology in this pedagogy. To address this issue, this study imparts a significant contribution in the overall body of knowledge by developing a technology integration framework for service learning programs. Our proposed framework comprises of three main components, i.e. (1) identification of common phases for service learning implementation, which are drawn on Kolb's (1984) experiential learning theory; (2) technology support layer and; (3) stakeholders’ involvement patterns in service learning. Design science research methodology was employed for developing our proposed Technology Integration Framework for Service Learning (TIFSL) in this study. Moreover, in order to evaluate our proposed framework, a case study was also conducted, where data was collected through semi-structured interviews and survey based questionnaires. Findings of this study demonstrate that three main components of our proposed framework determine the effective technology integration in service learning. Respondents from case study reflected on their own service learning implementation process and technology utilization throughout their service learning projects, which highlights constrains from current technologies for effective integration in service learning pedagogy.